Penggunaan Permainan Truth or Dare untuk Meningkatkan Kemampuan Keterampilan Berbicara Siswa pada Recount Text - Bua, Elia Toding (Jurnal Didaktika Pendidikan Dasar, 2022)
Speaking is one of the language skills which need a great attention since it is considered as the most difficult skill to be mastered by junior high school students. Pertinent to the researcher’s experience, the average score of the students’ results in preliminary observation is only 53.64. It was found that most of the students got difficulty in telling past events orally because they have poor vocabulary items, grammar, and pronunciation. The purpose of this research is to know how “Truth or Dare Game” can escalate the students’ speaking ability on recount text. This research employed Collaborative Classroom Action Research. The researcher and his collaborator worked together in designing the lesson plans, determining the criteria of success, implementing the action, observing, and reflecting. The subjects of this research comprised of 32 students. The research instruments were students’ speaking performance task consisting of three tasks and field notes.  The findings showed that the use of “Truth or Dare Game” can escalate the students’ speaking ability on recount text. It can be seen from the average score in Task 1 was 73.82; Task 2 was 78.51, and increased to 84.08 in Task 3. In conclusion, the research contributed to the English teachers that the strategy can be one of the appropriate solutions to solve the same problems related to the teaching of speaking, especially recount text. Future researchers are recommended to use this research as reference to accomplish further research at the same or different language skills and level of education.